Association between the functional capacity of dependant elderly people and the burden of family caregivers - Ana Cláudia Fuhrmann; Carla Cristiane Becker Kottwitz Bierhals; Naiana Oliveira dos Santos; Lisiane Manganelli Girardi Paskulin
The aim of this study was to characterize dependent elderly people and their main family caregivers and the association between functional capacity of the elderly and the burden of caregivers. This cross-sectional study was conducted with 112 elderly people and caregivers connected to a primary care service in Porto Alegre, Brazil. The applied instruments related to care and socioeconomic variables were Physical and Instrumental Activities of Daily Living (PADL and IADL) and the Burden Interview. The Spearman correlation coefficient was also used. Average age of the elderly individuals in this study was 81.41 years, while the average score for PADL was 10.36 and 6.25 for IADL. Of the 112 elderly individuals, 71.4% had severe dependence. Among caregivers, 75% were women, 61.6% were the sons or daughters with an average age of 57.98 and an average burden of 29.53, which is equivalent to moderate burden. Results revealed a significant correlation between functional capacity of the elderly and caregiver burden. It was verified that the higher the dependence of elderly people, the greater the burden of caregivers.